Identification of Polyamide 6 and Polyamide 66 Oligomers Using Ion Mobility Time-of-flight Mass Spectrometry and Risk Assessment Study of Their Migration from Kitchenware to Foodstuff - Song, Xuechao; Canellas, Elena; Nerín, Cristina (Jornada de Jóvenes Investigadores del I3A, 2020)
Ion mobility time-of-flight mass spectrometry has been used for the identification the PA 6 and PA 66 oligomers through their accurate m/z, CCS values and fragmentation pattern. An extraction method for the oligomers from sunflower oil, cooked beans, soup and whole milk has been developed with recoveries ranging from 87 to 102 %.